The impact of credit and debt on wealth accumulation - Leitz, Linda Y. (Kansas State University, 2016)
This study explored whether the use of debt, specifically mortgages and student loans, has a negative relationship with wealth accumulation over a consumer’s lifetime. The analysis looked at whether exploration questioned whether consumer debt is incongruent with good personal financial management and consumers should hold a philosophy of avoidance of debt in order to accumulate more wealth. Some financial planners believe in leveraging current assets in hopes of accelerating wealth accumulation. The latter approach is more congruent with a behavioral life-cycle hypothesis perspective (Shefrin & Thaler, 1988), which posits that consumers are the happiest when consumption remains relatively constant over a lifetime through use of debt and savings. To account for wealth accumulation across the lifespan, a measure of relative net worth was constructed by taking current net worth divided by current annual income divided by age. Relative net worth was used rather than net worth in order to allow comparisons between consumers of different ages and income. Data were collected from a sample of convenience, recruited from social media, friends and their acquaintances, and the clients of financial advisors who agreed to distribute the survey. Four ordinary least squares (OLS) regression analyses were conducted to determine the influence of current mortgage relative to the value of the home, mortgage obtained at the time of home purchase as a multiple of income, and student loans at graduation as a multiple of income on relative net worth accumulations. Results suggested that current mortgage debt that is 80% or less of home value, lack of a mortgage, and completing higher education without student debt are associated with higher relative net worth. Using a sample of convenience, the respondent pool was not nationally representative. In comparison to the United States population, the sample population is more highly educated, has a higher percentage of married and individuals in a committed relationship, contains more adults over the age of 50, and does not reflect the ethnic diversity of the United States. This study did not provide deep new insight into the factors contributing to wealth accumulation. It showed that mortgages and student loans alone do not have a large impact on wealth accumulation. This is evidenced by the low R² for all regressions (ranging from .00 to .07). Of the independent variables chosen for regression, the impact was not large and statistical significance for those factors was not present in all regressions. The results of this study do not provide direct support to the ability to use mortgages and student loans as part of wealth accumulation strategies. Future studies may be able to incorporate other elements with debt decisions as well as the impact of financial advice on the use and levels of debt as part of an integrated wealth accumulation strategy. The level of debt to positively impact socioeconomic status is also another area for future study.
Keywords: Wealth accumulation; Mortgages; Student debt; Debt